Manuscript of the Mushaf al-Qur’an from the Lingga Kingdom on Penyengat Island, Kepulauan Riau: Analysis of History, Rasm, and Qira'at - Hermawan, Wendy; Putra, Afriadi; Wilaela, (QOF, 2023)
The Lingga Kingdom is one of the Malay kingdoms that has many historical legacies that are intellectual property. One of them is the large number of al-Qur'an Mushaf manuscripts scattered in this area, especially on Lingga Island and Penyengat Island. This study focused on research on a manuscript found on Penyengat Island with inventory number M. 1 24 and an analysis of the use of rasm and qira`at as the formulation of the problem to be studied. This study was field research used qualitative methods with textological approaches, rasm science, and qira`āt science. Research data obtained from the results of observations, interviews, and documentation obtained during research. The data is reduced and described in detail then drawn a deductive conclusion. Judging from the use of the words hadhf, ziyādah, hamzah, badl, waṣl wa faṣl, and the writing of the qira`āt. This manuscript falls into the category of mushaf with mixed rasm, namely the use of rasm imlā`i and rasm ‘uthmāni simultaneously. Meanwhile, from the aspect of the type of qira`āt used, this manuscript follows the qira`at of Imam Ậṣim al-Kūfi through the narration of Imam Hafṣ.